The Use of Letter Block Media in Improving the Language Skills of Children Aged 5-6 Years in Paud Sinar Leksula Village Leksula Buru Selatan District - Novi Saleky; Lamberthus J. Lokollo; H. Abarua (International Journal of Education, Information Technology, and Others, 2023)
The aim of this research is "To determine the use of letter block media in improving language skills in children at PAUD Sinar, Leksula Village, Leksula District, South Buru Regency". The methods used by researchers to collect research data. The method used in this research is classroom action research (PTK). Classroom action research in English is called classroom action research. classroom action research (PTK) which has been carried out through the second cycle with two meetings, cycle I (15%) means that the language skills of children on average are still at the level of starting to develop and there are still children who have not yet developed. several things. So it can be concluded that research activities will continue in cycle two. This can be seen from the results of observation in cycle II (100%) which shows changes in the learning outcomes of children who are no longer at the undeveloped criteria, so that learning in cycle II is said to have been achieved successfully